Successful establishment and five-year sustainability of a neonatal-specific antimicrobial stewardship program in a low middle-income country - Faouzi I. Maalouf; Therese Saad; Ramia Zakhour; Khalid Yunis (Frontiers Media S.A., 2023)
Introduction: Antibiotic use varies substantially among neonatal intensive care units (NICUs) without any appreciable impact on outcomes. An increased use of antimicrobials has been reported in low-middle income countries. This raises the concern for potential overuse of antibiotics in a fragile patient population, thus increasing the rates of multidrug resistant organisms and affecting the developing microbiome. The presence of a neonatal-specific antimicrobial stewardship program can aid with the judicious use of antibiotics in the neonatal population and thus decrease the overuse of such medications.Methods: In this quality improvement project, we established and implemented a neonatal-specific antimicrobial stewardship program with the aim of reducing antimicrobial use in the neonatal intensive care units within a year of starting. Several interventions using a multidisciplinary approach included implementing standard algorithms, direct audit and feedback, and automated hard stops.Results: These series of interventions led to a 35% decrease in antimicrobial usage in the first 3 months and further decrease was seen with a median of 63% decline for a total of 5 years after project implementation. The use of the most commonly prescribed antibiotics, ampicillin and gentamicin, decreased by 63% and 79%, respectively. There was no evidence that this change in practice affected or jeopardized patient outcomes. Additionally, it showed sustainability and resilience despite the many challenges such as COVID-19 pandemic, political and financial unrest, and healthcare sector collapse.Discussion: This model-based and multidisciplinary low-cost approach can lead to marked improvement affecting neonatal outcomes and can be replicated in other similar centers.